Pharmacological evaluation of some central nervous system effects of Cotyledon Orbiculata - Kabatende, Joseph (University of the Western Cape, 2013)
Magister Pharmaceuticae - MPharm === The use of traditional medicine through the use of medicinal plants in Africa and especially in South Africa has long been considered an important characteristic of people's daily lives and socio-cultural heritage. Cotyledon Orbiculata is among the medicinal plants that are used by South African traditional practitioners for the treatment of epilepsy and painful conditions such as corns, warts, toothache, earache, boils and various other ailments. However, the claim of therapeutic successes of medicinal plants by traditional medicine practitioners are hardly subjected to scientific scrutiny. This study therefore, investigated the anti-epileptic property of Cotyledon Orbiculata by studying the effects of the methanol extract of the plant against chemically induced seizures by pentylenetetrazole, picrotoxin, bicuculline and N-methyl-DL-aspartic acid in mice. The study also investigated the analgestic effects of Cotyledon Orbiculata by studying the effect of the plant extract on pain induced by acetic acid and hot plate thermal stimulation. === South Africa